STRONGLY CLEAN ELEMENTS IN A CERTAIN BLOCK MATRIX RING - Nikkhah, Abolfazl; Davvaz, Bijan (IndoMS, 2016)
In this paper, we investigate the concepts of strongly clean, strongly π-regular and strongly J_n-clean related to the ring A=pmatrixR_RM_S 0Spmatrix. Moreover, we give several equivalent conditions such that an element αEnd(A)Â is strongly clean.DOI :Â http://dx.doi.org/10.22342/jims.22.2.259.151-156